Bronchiolitis obliterans syndrome and restrictive allograft syndrome after lung transplantation: why are there two distinct forms of chronic lung allograft dysfunction? - Sato, Masaaki (Ann Transl Med, 2020)
Bronchiolitis obliterans syndrome (BOS) had been considered to be the representative form of chronic rejection or chronic lung allograft dysfunction (CLAD) after lung transplantation. In BOS, small airways are affected by chronic inflammation and obliterative fibrosis, whereas peripheral lung tissue remains relatively intact. However, recognition of another form of CLAD involving multiple tissue compartments in the lung, termed restrictive allograft syndrome (RAS), raised a fundamental question: why there are two phenotypes of CLAD? Increasing clinical and experimental data suggest that RAS may be a prototype of chronic rejection after lung transplantation involving both cellular and antibody-mediated alloimmune responses. Some cases of RAS are also induced by fulminant general inflammation in lung allografts. However, BOS involves alloimmune responses and the airway-centered disease process can be explained by multiple mechanisms such as external alloimmune-independent stimuli (such as infection, aspiration and air pollution), exposure of airway-specific autoantigens and airway ischemia. Localization of immune responses in different anatomical compartments in different phenotypes of CLAD might be associated with lymphoid neogenesis or the de novo formation of lymphoid tissue in lung allografts. Better understanding of distinct mechanisms of BOS and RAS will facilitate the development of effective preventive and therapeutic strategies of CLAD.